2017
DOI: 10.1007/s13197-017-2720-7
|View full text |Cite
|
Sign up to set email alerts
|

Microbial analysis of meatballs cooled with vacuum and conventional cooling

Abstract: Vacuum cooling is a rapid evaporative cooling technique and can be used for pre-cooling of leafy vegetables, mushroom, bakery, fishery, sauces, cooked food, meat and particulate foods. The aim of this study was to apply the vacuum cooling and the conventional cooling techniques for the cooling of the meatball and to show the vacuum pressure effect on the cooling time, the temperature decrease and microbial growth rate. The results of the vacuum cooling and the conventional cooling (cooling in the refrigerator)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 25 publications
0
18
0
2
Order By: Relevance
“…During the cooling process, the water will start boiling when the pressure drops to the corresponding pressure of the water saturation temperature (flash point) (Ozturk & Hepbasli, ; Ozturk et al ., ). Lots of bubbles appeared to serve the function of disturbance and take away the heat.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…During the cooling process, the water will start boiling when the pressure drops to the corresponding pressure of the water saturation temperature (flash point) (Ozturk & Hepbasli, ; Ozturk et al ., ). Lots of bubbles appeared to serve the function of disturbance and take away the heat.…”
Section: Resultsmentioning
confidence: 97%
“…The process of bubbles generating from the bottom and then moving to the surface will strengthen the convection and allowed the water and pork to move rather than motionless during the stage of “before boiling” and “slug flows”. The temperature difference also exits between the surface and the centre of the meat (Song & Liu, ; Ozturk et al ., ). The lower temperature of the meat surface will help to the convective within meat.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, the vacuum cooling of cooked meat and the comparison with other cooling methods has been extensively reported. Ozturk, Ozturk, and Koçar () inspected the microbial growth rate of meatballs cooled by vacuum cooling and conventional cooling, respectively. Feng, Sun, Martín, and Zhang () observed that cooked sausages operated by immersion vacuum cooling in cold water can achieve a longer shelf life than immersion vacuum cooling in hot water and commercial cooling.…”
Section: Introductionmentioning
confidence: 99%
“…Soğutma çok hızlı bir Ģekilde gerçekleĢtiği için de ürün içerisinde mikrobiyal geliĢmeler yavaĢlamakta bu nedenle de ürünün raf ömrü artmaktadır. Geleneksel soğutma yöntemleriyle karĢılaĢtırıldığında, vakum soğutma mantar soğutma süresini önemli ölçüde azaltabilir ve mikrobiyal büyüme oranını düĢürebilir [2].…”
unclassified